Telephone interventions for adherence to colpocytological examination - Thais Marques Lima; Ana Izabel Oliveira Nicolau; Francisco Herlânio Costa Carvalho; Camila Teixeira Moreira Vasconcelos; Priscila de Souza Aquino; Ana Karina Bezerra Pinheiro
ABSTRACT Objective: to test the effects of behavioral and educational intervention by telephone on adherence of women with inappropriate periodicity to colpocytological examination. Method: quasi-experimental study with a sample of 524 women, selected with the following inclusion criteria: be aged between 25 and 64 years, have initiated sexual activity, have inappropriate periodicity of examination and have mobile or landline phone. The women were divided into two groups for application of behavioral and educational intervention by telephone. It was used an intervention script according to the principles of Motivational Interviewing. Results: on comparing the results before and after the behavioral and educational interventions, it was found that there was a statistically significant change (p = 0.0283) with increase of knowledge of women who participated in the educational intervention. There was no change in the attitude of women of any of the groups and there was an increase of adherence to colpocytological examination in both groups (p < 0.0001), with greater adherence of women participating in the behavioral group (66.8%). Conclusion: the behavioral and educational interventions by phone were effective in the adherence of women to colpocytological examination, representing important strategies for permanent health education and promotion of care for the prevention of cervical cancer.